Respostas
respondido por:
0
4x + 3 = - 1 + 5
4x + 3 = 4
4x = 4 - 3
x = 1 /4
8x - 5 = 9 + 2
8x - 5 = 11
8x = 11 + 5
8x = 16
x = 16/8
x = 2
4x + 3 = 4
4x = 4 - 3
x = 1 /4
8x - 5 = 9 + 2
8x - 5 = 11
8x = 11 + 5
8x = 16
x = 16/8
x = 2
respondido por:
0
4x+3=-1
4x=-1-3
4x=-4
x=-4/4
x=-1
Resposta: -1
8x-5=9
8x=9+5
8x=14
x=14/8 = 7/4
Resposta: 7/4
4x=-1-3
4x=-4
x=-4/4
x=-1
Resposta: -1
8x-5=9
8x=9+5
8x=14
x=14/8 = 7/4
Resposta: 7/4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás